Report Trip to Tanah Datar, 13-15 June 2012 - ISITI, -CoERI (ISITI-CoERI, 2012)
The Telecommunication Technology Committee (TTC) Japan invited Universiti Malaysia Sarawak (UNIMAS) who are working with them on the Asia Pacific Telecommunity J3 Project. The UNIMAS team was led by Dr Fitri Suraya Mohamad, and the main purpose of the visit was to attend a meeting with community leaders of Tanah Datar, Sumatra, from 13th to 15th June 2012. The key agenda of the meeting was to present and demonstrate an e-Education application (MyKLiKs) which was developed by the APT J3 Malaysia team of researchers who are from the Institute of Social Informatics and Technological Innovations, Centre of Excellence for Rural Informatics (ISITI-CoERI), UNIMAS. The E-Education application has been installed and implemented at two remote schools in Bario, the research location for the APT J3 project. Bario is located in the centre of the Kelabit Highlands in the north east of Sarawak Malaysia, very close to the international border with Indonesian Kalimantan, and 3280 feet above sea level and Kuching, the capital of the East Malaysian state of Sarawak. The distance between Bario and Kuching is approximately 690km (379 miles)